2022
DOI: 10.30762/jeels.v7i2.2182
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on The Role of Sociocultural Factors In ESL Pre-Service Teachers’ Beliefs And Practice

Abstract: Pre-service teachers are often involved in the continuous construction and reconstruction of their identities that are shaped by various internal and external factors. This study explores sociocultural factors that influence pre-service teachers' beliefs about teaching and learning namely 1) previous schooling experience, 2) teacher education, and 3) curriculum specifications. Participants of the study were three pre-service teachers studying at a local university in Malaysia. Data were collected through face-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Most of the students also fixed their drafts, but some students also tried to revise their drafts using automated online feedback such as google docs, Grammarly, etc. These interview results are in line with Jodaie et al (2011), Mohammad and Rahman (2016), Elhawwa et al (2018), Listiani (2017), Luan and Ishak (2018), Tursina et al (2019), Hartono et al (2019, Sabarun (2020), & (Yunus, 2020) stating that most of the students had positive attitudes towards their lecturer direct corrective feedback because it is very helpful, beneficial for the learners; students preferred to have comprehensive, direct, and specific feedback; and students also felt satisfied. This finding supports idea that by giving direct corrective feedback, the students will acquire grammar with specific features (Sheen, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most of the students also fixed their drafts, but some students also tried to revise their drafts using automated online feedback such as google docs, Grammarly, etc. These interview results are in line with Jodaie et al (2011), Mohammad and Rahman (2016), Elhawwa et al (2018), Listiani (2017), Luan and Ishak (2018), Tursina et al (2019), Hartono et al (2019, Sabarun (2020), & (Yunus, 2020) stating that most of the students had positive attitudes towards their lecturer direct corrective feedback because it is very helpful, beneficial for the learners; students preferred to have comprehensive, direct, and specific feedback; and students also felt satisfied. This finding supports idea that by giving direct corrective feedback, the students will acquire grammar with specific features (Sheen, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, (Listiani, 2017), (Tursina et al, 2019), (Hartono et al, 2019), and (Sabarun, 2020) found that university students are satisfied, preferred to be given direct corrective feedback, and felt assessed after being given the direct corrective feedback in their writing. In line with the previous finding, Yunus (2020) found that high school students are preferred to be given direct corrective feedback since it is comprehensive and easier to be understood. However, only a few studies have investigated direct corrective feedback in a qualitative design, this research fills in the gap, especially during online learning and used different participants in terms of level and writing course.…”
Section: Introductionsupporting
confidence: 88%